Adapting to Digitalization: Employee Readiness and Challenges in a Philippine Insurance Company - Jesus Briones; Cristy M Llorin; Benly G Angustia; Michelle G Carig; Clouie L Flores; Monique M Galapon (Journal of Governance Risk Management Compliance and Sustainability, 2026)
The rapid digital transformation of the insurance industry introduces new operational and compliance risks that require a digitally prepared workforce. However, limited evidence links employee digital readiness to governance, risk, and compliance challenges during insurance digitalization. This study examined how employees’ digital readiness relates to perceived challenges that may affect operational resilience and compliance in a Philippine insurance company. A survey of 79 operations employees used validated Likert-scale measures of digital readiness (knowledge, skills, and attitudes) and perceived barriers (technological, organizational, and individual), with reliability assessed using Cronbach’s alpha. Data were analyzed using frequency and percentage, weighted mean, and Pearson correlation coefficient. Results indicate that employees demonstrated a moderate level of digital readiness while technological barriers emerged as the most significant challenges during the digitalization process. Correlation analysis revealed significant positive relationships between readiness dimensions and perceived challenges on digitalization adaptation. Based on these findings, the researchers proposed strategies to strengthen employee readiness and reduce adaptation challenges to support the company’s digitalization initiatives. Findings of this study highlight the importance of strengthening workforce digital capabilities as part of risk-informed governance strategies for a regulated sector like the insurance industry. Theoretically, this study advances the Technology Acceptance Model by demonstrating that digital readiness is an organizational capability that shapes perceived barriers relevant to operational resilience and compliance in digital transformation initiatives. Practically, this study provides insights on how similar institutions enhance digital maturity, align employee readiness with organizational needs, and ensure smoother digital transformation.